Lithium and boron in calcified tissues of vicuna and its relation to the chronic exposure by water ingestion in the Andean lithium triangle - López Steinmetz, Romina Lucrecia (2019)
Vicuna is a wild, endangered species of Andean camelid living in the hyperarid Andean plateau. In the central part of the plateau, the Lithium Triangle defines a zone with lithium‐rich salt pans. Brine pools naturally form within the salt pans, and the adaptation strategy of vicuna consists of drinking from brine pools. Together with reporting the first chemical data on vicuna bones and teeth, we analyzed lithium, boron, and arsenic in water and brines, with the aim of assessing their relation to chronic exposure by water ingestion. We collected and analyzed bones of vicuna specimens lying in an Andean salt pan, together with brine and water samples. Brine and water samples are highly saline and contain large amounts of lithium, boron, and arsenic. Lithium (13.50–40 mg kg–1 ) and boron (40–46.80 mg kg–1 ), but not arsenic, were found in the vicuna bones and teeth. Based on our results and on previously reported data on human tissues in the Andes, we conducted statistical assessments of the relationships between lithium and boron in body tissues and water samples, and discuss their environmental significance in the context of the Lithium Triangle.